Knowledge of reproductive and sexual rights among University students in Ethiopia: institution-based cross-sectional - Adinew Yohannes Mehretie; Worku Abebaw Gebeyehu; Mengesha Zelalem Birhanu (BMC, 2013)
Abstract Background People have the right to make choices regarding their own sexuality, as far as they respect the rights of others. The knowledge of those rights is critical to youth's ability to protect themselves from unwanted reproductive outcomes. Reproductive health targeted Millennium Development Goals will not be achieved without improving access to reproductive health. This study was aimed to assess knowledge of reproductive and sexual rights as well as associated factors among Wolaita Sodo University students. Methods An institution-based cross-sectional survey was conducted among 642 regular undergraduate Wolaita Sodo University students selected by simple random sampling. A pretested and structured self-administered questionnaire was used for data collection. Data were entered using EPI info version 3.5.3 statistical software and analyzed using SPSS version 20 statistical package. Descriptive statistics was used to describe the study population in relation to relevant variables. Bivariate and multivariate logistic regression was also carried out to see the effect of each independent variable on the dependent variable. Results More than half (54.5%) of the respondents were found to be knowledgeable about reproductive and sexual rights. Attending elementary and high school in private schools [AOR: 2.08, 95% CI: 1.08, 3.99], coming from urban areas [AOR: 1.46, 95% CI: 1.00, 2.12], being student of faculty of health sciences [AOR: 2.98, 95% CI: 1.22, 7.30], participation in reproductive health clubs [AOR: 3.11, 95% CI: 2.08, 4.65], utilization of reproductive health services [AOR: 2.34, 95% CI: 1.49, 3.69] and discussing sexual issues with someone else [AOR: 2.31, 95% CI: 1.48, 3.62], were positively associated with knowledge of reproductive and sexual rights. Conclusion The level of knowledge of students about reproductive and sexual rights was found to be low. The Ministry of Education has to incorporate reproductive and sexual rights in the curricula of high schools and institutions of higher learning.